Adiponectin reverses β-Cell damage and impaired insulin secretion induced by obesity - Munhoz, Ana Cláudia; Serna, Julian D. C.; Vilas-Boas, Eloisa Aparecida; Caldeira da Silva, Camille C.; Santos, Tiago G.; Mosele, Francielle C. [UNESP]; Felisbino, Sergio L. [UNESP]; Martins, Vilma Regina; Kowaltowski, Alicia J. (Wiley, 2023)
Obesity significantly decreases life expectancy and increases the incidence of age-related dysfunctions, including β-cell dysregulation leading to inadequate insulin secretion. Here, we show that diluted plasma from obese human donors acutely impairs β-cell integrity and insulin secretion relative to plasma from lean subjects. Similar results were observed with diluted sera from obese rats fed ad libitum, when compared to sera from lean, calorically restricted, animals. The damaging effects of obese circulating factors on β-cells occurs in the absence of nutrient overload, and mechanistically involves mitochondrial dysfunction, limiting glucose-supported oxidative phosphorylation and ATP production. We demonstrate that increased levels of adiponectin, as found in lean plasma, are the protective characteristic preserving β-cell function; indeed, sera from adiponectin knockout mice limits β-cell metabolic fluxes relative to controls. Furthermore, oxidative phosphorylation and glucose-sensitive insulin secretion, which are completely abrogated in the absence of this hormone, are restored by the presence of adiponectin alone, surprisingly even in the absence of other serological components, for both the insulin-secreting INS1 cell line and primary islets. The addition of adiponectin to cells treated with plasma from obese donors completely restored β-cell functional integrity, indicating the lack of this hormone was causative of the dysfunction. Overall, our results demonstrate that low circulating adiponectin is a key damaging element for β-cells, and suggest strong therapeutic potential for the modulation of the adiponectin signaling pathway in the prevention of age-related β-cell dysfunction.
Keywords: adiponectin; calorie restriction; diabetes; obesity; oxidative phosphorylation